On Possible Forms of Expounding Philosophy - Radovanović, Biljana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This paper deals with the analysis of various ways of expounding philosophical content. We start by distinguishing between oral and written methods of presenting philosophical knowledge and then proceed to categorize philosophical texts based on the criterion of exposition. In the central part of the paper, we analyze the fundamental philosophical-scientific forms of expounding philosophical content: prolegomena, treatises, essays, meditations, aphorisms, autobiographies, letters, etc. The goal of this paper is to emphasize the connection between scientific forms and specific philosophical content, as well as the close correlation between the form of exposition and the purpose of a particular text. In the concluding chapter, we address the question: What allows philosophical content to be expounded in various ways? In answering this question, we highlight an important characteristic of philosophy that makes it more akin to art than to science.